Experimental Analysis of Touch-Screen Gesture Designs in Mobile Environments - Bragdon, Andrew; Nelson, Eugene; Li, Yang; Hinckley, Ken (CHI '11 Proceedings of the SIGCHI Conference on Human Factors in Computing Systems, 2011)
Direct-touch interaction on mobile phones revolves around screens that compete for visual attention with users‟ real-world tasks and activities. This paper investigates the impact of these situational impairments on touch-screen interaction. We probe several design factors for touch-screen gestures, under various levels of environmental demands on attention, in comparison to the status-quo approach of soft buttons. We find that in the presence of environmental distractions, gestures can offer significant performance gains and reduced attentional load, while performing as well as soft buttons when the user‟s attention is focused on the phone. In fact, the speed and accuracy of bezel gestures did not appear to be significantly affected by environment, and some gestures could be articulated eyes-free, with one hand. Bezel-initiated gestures offered the fastest performance, and mark-based gestures were the most accurate. Bezel-initiated marks therefore may offer a promising approach for mobile touch-screen interaction that is less demanding of the user‟s attention.